The study spatial and temporal changes of water quality in Choghakhor wetland using water quality index (WQI) - Pejman Fathi; Eisa Ebrahimi; Norolah Mirghafari; Alireza Esmaeili (بوم‌شناسی آبزیان, 2016)
In order to investigation of water quality of the Choghakhor wetland by use of WQI, ten stations were selected. Sampling was done every 45 days since April 2010 until March 2011 with 3 replications at each station. Water Quality Index (WQI) was calculated using nine water quality parameters (Nitrate, Nitrite, Alkalinity, Hardness, Turbidity, Conductivity, Dissolved Oxygen, pH and Biochemical Oxygen Demand). For this propose, the relative weight assigned to each parameter ranged from 1 to 4 based on the importance of these parameters for aquatic life and their role in use of water resource for human life. The results of analyses of variance (ANOVA) showed a significant difference between different stages (p< 0.01). The results take the water quality of wetland in two categories: very poor and inappropriate. Based on this result, water quality of Choghakhor wetland was not suitable for human uses such as drinking. The most important factor in assessment of water quality in this index was BOD5.